2001
DOI: 10.1007/s00277-001-0400-0
|View full text |Cite
|
Sign up to set email alerts
|

Secondary acute myeloid leukemia and myelodysplasia after autologous peripheral blood progenitor cell transplantation

Abstract: Secondary myelodysplastic syndrome (MDS) and acute leukemia (AL) are well-known complications of antineoplastic therapy. The incidence of these serious complications after autologous hematopoietic transplantation ranges from 1.1% to 24%. Prior chemotherapy is its most likely cause, but other variables related to these long-term complications are seriously discussed. There is evidence that priming of progenitor cells isolated from peripheral blood with chemotherapy is also related to a higher risk of secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 14 publications
0
19
0
3
Order By: Relevance
“…The incidence of secondary MDS/AML after autologous transplantation ranges from 1.1 to 24%. 20 Recently, chemomobilization with etoposide was found to increase the risk of treatment-related MDS/AML in autologous transplantation. 21 Etoposide and Ara-C delivered before the mobilization of peripheral blood stem cell in our study may have increased the risk of secondary MDS.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of secondary MDS/AML after autologous transplantation ranges from 1.1 to 24%. 20 Recently, chemomobilization with etoposide was found to increase the risk of treatment-related MDS/AML in autologous transplantation. 21 Etoposide and Ara-C delivered before the mobilization of peripheral blood stem cell in our study may have increased the risk of secondary MDS.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this, several studies have identified a decreased dose of infused HSCs as a risk factor for t-AML/ MDS. 3,14,18 In addition, a recent report found an increased risk of t-AML/MDS in patients who required more than 5 days of apheresis, suggesting that a difficult stem cell harvest is a marker of marrow which has sustained significant genotoxic damage. 25 These observations support the notion that genotoxic damage initiated by pretransplant therapies may be amplified by the engraftment process, leading to the emergence of clonal abnormalities important in t-AML/MDS pathogenesis.…”
Section: Factor References Commentsmentioning
confidence: 99%
“…TBI 1,4,12,[15][16][17]20 Quantity of pre-transplant chemotherapy 2,12,13,15,18,25 Pre-transplant radiation therapy 4,8,9,16,25 Lower stem cell content/difficult stem cell collection 3,14,18,25 'Difficult' defined as requiring 45 days of apheresis. Pre-transplant alkylating agent exposure 2,13,20,22 PBSC product 5,6,11,20 Not found to be a risk factor by Sevilla et al 18 Trend (P ¼ 0.12) reported by Metayer et al 20 Time from diagnosis to transplant/number of relapses 9,12,14 Delayed platelet or ANC recovery post-transplant 2,14,19 Etoposide exposure 8,17 Exposure during priming chemotherapy or conditioning regimen. Pre-transplant fludarabine exposure 14,17 Refractory lymphoma 11,15 Abbreviations: AML/MDS ¼ acute myeloid leukemia and myelodysplasia; ASCT ¼ autologous stem cell transplantation; PBSC ¼ peripheral blood stem cell; TBI ¼ total body irradiation.…”
Section: Factor References Commentsmentioning
confidence: 99%
“…The AML are hematologic malignancies characterized by the uncontrolled myeloid blast proliferation in the bone marrow and in peripheral tissues. (Sevilla et al, 2002) Differ according to the cytological, immunophenotypic and cytogenetic characteristics. (Paietta, 1995;Head, 1996) On the other hand the MDS are dis-hematopoietics processes of bone marrow, characterized by alteration in the maturation and differentiation of hematopoietic cell lines (with involvement of one, two or all three blood cell lineages) and in some cases, by the presence of bone marrow blasts, without showing acute leukemia criteria.…”
Section: Secondary Leukemiasmentioning
confidence: 99%